Pelaksanaan Magang pada Rangkaian Proses Pengeleman Outsole (Rubber) dan Midsole (Phylon) di Departemen Stockfit PT X - Isnaeni Zahrotun Maulidiyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The shoe manufacturing industry demands a planned, integrated, and consistent production system in maintaining product quality. One of the crucial stages is the gluing process between the outsole (rubber) and the midsole (phylon), which determines the adhesive strength, comfort, and durability of the shoe. This study aims to analyze the implementation of internship activities in a series of gluing processes in the Stockfit Department of PT X. The research method uses a qualitative descriptive approach with data collection techniques through direct observation, involvement in production activities, and systematic field recording during the internship period. The analysis was carried out by linking the field findings with the operations management theory of Heizer and Render, the Crosby concept of quality management, and the principles of continuous improvement from Deming and Imai. The results of the study show that the gluing process has been systematically arranged, starting from material adjustment, primary application, the use of two types of glue, the rubber cutting process, to the final pasting. However, problems were found such as dependency between processes, inconsistency in glue thickness, as well as the influence of machine conditions and operator skills. These problems have the potential to reduce production efficiency and the quality of the final product. Therefore, it is necessary to strengthen process control and apply the principle of continuous improvement to improve overall production performance.